Modified IOTN: an orthodontic treatment need index for use in oral health surveys - Burden DJ, Pine CM, Burnside G (Blackwell Synergy, 2001)
This paper reports the results of a study of the reliability of a modified Key words: orthodontics; orthodontic version of the Index of Orthodontic Treatment Need (IOTN) for use in oral health treatment need; oral health surveys surveys